Penyesuaian akademik pada mahasiswa tahun pertama: Bagaimana peran efikasi diri? - Cindy Claudia Aurelia Yasin; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2023)
Abstract Individuals who adapt well in an academic environment learn in an efficient way, and can solve academic difficulties well. Self-efficacy helps students meet academic requirements and increases confidence in their own potential. The purpose of this study was to determine the relationship between self-efficacy and academic adjustment in first-year students. The subjects in this study were students of Class 2022 Faculty of Psychology University of August 17, 1945 Surabaya. The sampling technique in this study used a simple random sampling technique with a total of 205 respondents. The data collection instrument used a self-efficacy scale and an academic adjustment scale prepared by researchers using a Likert scale model. The data analysis technique used Spearman’s Rho non-parametric correlation analysis with the help of SPSS. The results of this study indicate a positive relationship between self-efficacy and academic adjustment in first-year students. The higher the student’s self-efficacy, the higher the level of academic adjustment. Vice versa, the lower the student’s self-efficacy, the lower the level of academic adjustment. Keywords: Self-efficacy; Academic adjustment; First year students. Abstrak Individu yang beradaptasi dengan baik dalam lingkungan akademik belajar dengan cara yang efisien, serta dapat menyelesaikan kesulitan akademik dengan baik. Efikasi diri membantu mahasiswa dalam memenuhi persyaratan akademik serta meningkatkan keyakinan akan potensi diri. Tujuan penelitian ini untuk mengetahui hubungan efikasi diri dengan penyesuaian akademik pada mahasiswa tahun pertama. Subjek dalam penelitian ini adalah mahasiswa Angkatan 2022 Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya. Teknik sampling pada penelitian ini menggunakan teknik simple random sampling berjumlah 205 responden. Instrumen pengumpulan data menggunakan skala efikasi diri dan skala penyesuaian akademik yang disusun oleh peneliti menggunakan model skala likert. Teknik analisis data menggunakan analisis korelasi non parametrik Spearman’s Rho dengan bantuan SPSS. Hasil penelitian ini menunjukan adanya hubungan positif antara efikasi diri dengan penyesuaian akademik pada mahasiswa tahun pertama. Semakin tinggi efikasi diri mahasiswa, maka semakin tinggi tingkat penyesuaian akademik. Begitupun sebaliknya semakin rendah efikasi diri mahasiswa, maka semakin rendah tingkat penyesuaian akademik. Kata kunci: Efikasi diri; Penyesuaian akademik; Mahasiswa tahun pertama.